Efficient Implementation of the Singular Value Decomposition on a Reconfigurable System - Bobda, Christophe; Linarth, Andre Guilherme; et al. (Proceedings of the International Conference on Field Programmable Logic and Applications (FPL2003), 2003)
We present a new implementation of the singular value decomposition (SVD) on a reconfigurable system made upon a Pentium processor and a FPGA-board plugged on a PCI slot of the PC. A maximum performance of the SVO is obtained by an efficient distribution of the data and the computation across the FPGA resource. Using the reconfiguration capability of the FPGA help us implement many operators on the same device. © Springer-Verlag Berlin Heidelberg 2003.
UnivIS-Import:2015-04-16:Pub.2003.tech.IMMD.inform.effici